Pendidikan Agama Kristen dan Pembimbingan Pelayan Gereja dalam Pembentukan Karakter Remaja - Sepri Karl Heinz Malelak (Fakultas Keguruan dan Ilmu Pendidikan Kristen IAKN Palangka Raya, 2022)
The aim of this research is to find out how the implementation of Christian religious education is related to the formation of adolescent character, how guidance by church servants is related to the formation of adolescent character, how is the relationship between the Implementation of Christian Religious Education and Guidance by Church Ministers together with the formation of adolescent character. Data was collected at the location and from teenagers who are the population, using a Likert scale, interviews and also documentation studies and then analyzed. The results of the research were that there was a very low relationship and there was no significant relationship between the Implementation of Christian Religious Education and the character formation of teenagers, there was a strong relationship and there was a significant relationship between Guidance by Church Servants and the character formation of teenagers, there was a strong relationship and there was a relationship There is a significant relationship between the Implementation of Christian Religious Education and Guidance by Church Servants together with the character formation of teenagers in the Bright Future Congregation of the Kupang New Testament Christian Church. Referrals to the church and related parties to improve the implementation of Christian religious education and guidance by church servants by paying attention to the needs and development of teenagers with Christian character.